Case report: Personalized management of treatment resistance in advanced NSCLC patients with mutated epidermal growth factor receptor: special examples and literature review - Jun Wang; Jun Wang; Xiaojing Li; Shuang Dong; Sheng Hu; Fengming Ran; Yu Qian (Frontiers in Oncology)
The treatment landscape of non-small cell lung cancer (NSCLC) has shifted significantly from empirical, histology-driven, and clinician-directed cytotoxic regimens to a stratified approach predicated on molecular profiling of tumor genetics and immune biomarkers, by the former can indicate targeted therapy that bull’s eye hits the arrow, while the latter can hint the benefit amplitude of immune checkpoint inhibitors (ICBs). While third-generation epidermal growth factor receptor tyrosine kinase inhibitors (EGFR TKIs) have become the cornerstone of frontline therapy for patients harboring classic sensitive EGFR mutations, all tumors ultimately develop acquired resistance to these approaches, which can be categorized into three primary mechanism subclasses. The first subclass involves the acquisition of target mutations that lead to changes in the kinase domain, thereby hindering drug binding. The second mechanism, known as bypass resistance, entails tumor clones utilizing alternative signaling pathways for proliferation. Lastly, the third acquired mechanism pertains to histological transformation, such as the emergence of small cell lung cancer (SCLC) clones. The transformation of pathological types has brought great confusion to the clinical diagnosis and treatment process. We report a case of advanced lung adenocarcinoma with EGFR-sensitive mutation that transformed into small cell lung cancer after EGFR-TKIs treatment. Subsequent treatment revealed the presence of both adenocarcinoma and small cell carcinoma through needle biopsies at various metastatic sites. Based on the pathological, the patient received combination therapy with anlotinib at different times and achieved a long survival time.